2011
DOI: 10.1021/ic102381j
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Electronic Structure Studies of Copper(II) Binding to His111 in the Human Prion Protein Fragment 106−115: Evaluating the Role of Protons and Methionine Residues

Abstract: The prion protein (PrP(C)) is implicated in the spongiform encephalopathies in mammals, and it is known to bind Cu(II) at the N-terminal region. The region around His111 has been proposed to be key for the conversion of normal PrP(C) to its infectious isoform PrP(Sc). The principal aim of this study is to understand the role of protons and methionine residues 109 and 112 in the coordination of Cu(II) to the peptide fragment 106-115 of human PrP, using different spectroscopic techniques (UV-vis absorption, circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 134 publications
9
52
0
Order By: Relevance
“…Further mutagenesis of His-111 seems to break the neurotoxicity of PrP(106-126) [68]. Copper ion binding to the imidazole side chain of histidine is well-known, and our results for PrP(111-126) are consistent with other prion peptide sequences containing histidine [68,75,76]. …”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Further mutagenesis of His-111 seems to break the neurotoxicity of PrP(106-126) [68]. Copper ion binding to the imidazole side chain of histidine is well-known, and our results for PrP(111-126) are consistent with other prion peptide sequences containing histidine [68,75,76]. …”
Section: Resultssupporting
confidence: 84%
“…Further, the addition of Cu 2+ to PrP(113-127) showed toxicity that may be due to the presence of unbound copper ions (Figure 5B). Therefore, the toxicity of PrP(111-126) may be due to the chelation of the cellular metal ions by the histidine residue, as the copper-bound peptide was nontoxic [68,75,76]. The prion peptides can also act as an antioxidant, enhancing the survival of the astrocytes by binding potentially harmful Cu 2+ ions and by quenching the free radicals generated as a result of copper redox cycling [79].…”
Section: Resultsmentioning
confidence: 99%
“…employed EPR spectroscopy along with other spectroscopic techniques to evaluate Met binding with Cu(II) in the hPrP fragment 106–115 . The authors suggested a weak axial interaction between Met 109 and copper while excluding any involvement of Met 112 and Met 109 in equatorial coordination to Cu(II) . Very recently, Remelli et al .…”
Section: Copper Coordination With Prpmentioning
confidence: 99%
“…(2) the mutants A117V and M129V cause GSS [49,50,51] and CJD [52,53] respectively, (3) the β-sheet core of PrP Sc consists of three layers of β-strands E1(116-119), E2(129-132) and E3(160-164) [54], where E1 and E2 are in the hydrophobic region (109-136), (4) H111 is a residue of copper binding sites [55,56,57,58], (5) Y128 is in the center of HB-and-SB-network of HB(Y128-D178), SB(D178-R164), HB(Y128-R164), HB(Y128-H177), HB(H177-N154) [59,60,61,62], (6) A133 and S132 have HBs with R220 and a water binding site with G131 [63,64], in PrP(113-132) the hydrophobic cluster with vdWs rendering of atoms in residues 113-127 interacts with the first β-strand (see Figure 2(B) of [65]), M129 makes interactions with the side chain of V122 and pulls the N-terminus into the β-sheet [61] and M129 is very close to Y163 [31], (7) conservation of the Gly-rich region PrP(119-131) is required for uptake of prion infectivity [3,66,67] is shown by the physical or chemical properties of numerous mutations in the PrP(119-131) Gly-rich region [3], (8) one O-linked sugar at Ser135 can affect the coil-to-β structural transition of the prion peptide, but at Ser132 the effect is opposite [68], etc., and (9) the NMR structure of HuPrP(110-136) in dodecylphosphocholine micelles was known (2LBG.pdb) [69] and we do MD simulations for it as follows.…”
Section: Molecules In This Parts Of the Truncated Octahedral Box Of Tmentioning
confidence: 99%